Robotic Milking Implementation in the Sverdlovsk Region - Skvortcov, Egor Artyomovich; Skvortcova, Ekaterina Gennadyevna; Nabokov, Vladimir Innokentyevich; Krivonogov, Pavel Sergeevich (Economy of Regions, 2017)
We research topic is relevant due to a high rate of the implementation of milking robots (automatic milking system, AMS) in Western Europe and in the Middle Urals. As of January 1, 2016, 21 milking robot systems of six different brands of foreign production were installed in the region. Milking robotics is used in small, medium and large enterprises (by the number of personnel), in contrast to Western Europe, where it is mainly used on the farms of family type. The article examines the socioeconomic causes of the introduction of robotics, as well as the impact of the use of robots to the economic indicators of milk production. We expert survey has revealed as the main reasons for the introduction of robotics, a desire to reduce the risks of personnel (45.5 %) and a shortage of staff (18.2 %). We analysis of the utilization efficiency of fixed assets in all organizations introduced robots has shown both a decrease of capital productivity after the introduction of milking robots for 15-60 % or more, and the reduce of the profit rate in 9 out of 11 of the analysed organizations because of the high capital intensity of robotics projects. We analysis of labour indicators and the net cost of milk is carried out in 45.5 % of organizations, where we have obtained the consistent results of the use of robotics. We authors have analysed the direct costs for the production of 1 quintal of milk. In a group of 5 companies, on a robotic farm, it is 5.1 % lower than in a conventional farm. We complexity of the production of milk on a robotic farm is lower by 48.7 %, and labour productivity per person is higher on 95.3 % than on conventional farms. We results of the study can be used as the recommendations for agricultural organizations to use robotics milking to reduce the deficit of staff and to minimize the impact of personnel risks on production results. We growth of the importance of the reasons for the introduction of milking robots and a high capital intensity of import robotics can justify the need for a national milking robotics.